Simvastatin inhibits oxidative stress via the activation of nuclear factor erythroid 2‐related factor 2 signaling in trophoblast cells. Issue 1 (10th November 2015) - Chigusa, Yoshitsugu; Kawasaki, Kaoru; Kondoh, Eiji; Mogami, Haruta; Ujita, Mari; Fujita, Kohei; Tatsumi, Keiji; Takeda, Satoru; Konishi, Ikuo
Abstract: Aim: Nuclear factor erythroid 2‐related factor 2 (Nrf2) is a key transcriptional regulator against oxidative stress through the induction of antioxidant and cytoprotective genes, such as heme oxygenase 1 (HO‐1), glutamyl cysteine ligase catalytic (GCLC), and glutamyl cysteine ligase modulatory (GCLM). Nrf2 signaling is disrupted in pre‐eclamptic placentas, although increased oxidative stress is implicated in pre‐eclampsia. The aims of the study were: (i) to investigate the mechanism that underlies the impaired Nrf2 signaling in pre‐eclamptic placentas, and (ii) to examine the potential therapeutic role of statin for pre‐eclampsia. Material and Methods: Human choriocarcinoma JAR cells were cultured under normoxia (20% O2 ) or hypoxia (1% O2 ). Small‐interfering ribonucleic acids were used to knockdown Nrf2. Real‐time quantitative reverse transcriptase polymerase chain reaction and Western blotting were used to evaluate the influence of oxidative stress (H2 O2 100 μM) and simvastatin (50 μM) on Nrf2 and its target genes. Reactive oxygen species levels were analyzed by flow cytometry in immortalized human trophoblast TCL1 cells treated with or without H2 O2 (100 μM) ± simvastatin (50 μM). Results: Nuclear factor erythroid 2‐related factor 2 activation was significantly suppressed under hypoxic conditions. Nrf2 knockdown resulted in insufficient enhancement of HO‐1, GCLC and GCLM expression under oxidative stress. In contrast, Nrf2 signaling was augmented by simvastatin, which suppressed the induction of oxidative stress in trophoblasts. Conclusion: Hypoxia is one of the important negative regulators of Nrf2 activation, and simvastatin inhibits oxidative stress through the activation of Nrf2 signaling in trophoblasts, indicating the potential therapeutic role of statin for pre‐eclampsia.